TMEM70 deficiency: long-term outcome of 48 patients - Magner, Martin; Dvorakova, Veronika; Tesarova, Marketa; Mazurova, Stella; Hansikova, Hana; Zahorec, Martin; Brennerova, Katarina; Bzduch, Vladimir; Spiegel, Ronen; Horovitz, Yoseph; Mandel, Hanna; Eminoğlu, Fatma Tuba; et al. (Journal of inherited metabolic disease, 2015)
OBJECTIVES: TMEM70 deficiency is the most common nuclear-encoded defect affecting the ATP synthase. In this multicentre retrospective study we characterise the natural history of the disease, treatment and outcome in 48 patients with mutations in TMEM70. Eleven centers from eight European countries, Turkey and Israel participated. RESULTS: All 27 Roma and eight non-Roma patients were homozygous for the common mutation c.317-2A > G. Five patients were compound heterozygotes for the common mutation and mutations c.470 T > A, c.628A > C, c.118_119insGT or c.251delC. Six Arab Muslims and two Turkish patients were homozygous for mutations c.238C > T, c.316 + 1G > T, c.336 T > A, c.578_579delCA, c.535C > T, c.359delC. Age of onset was neonatal in 41 patients, infantile in six cases and two years in one child. The most frequent symptoms at onset were poor feeding, hypotonia, lethargy, respiratory and heart failure, accompanied by lactic acidosis, 3-methylglutaconic aciduria and hyperammonaemia. Symptoms further included: developmental delay (98%), hypotonia (95%), faltering growth (94%), short stature (89%), non-progressive cardiomyopathy (89%), microcephaly (71%), facial dysmorphism (66%), hypospadias (50% of the males), persistent pulmonary hypertension of the newborn (22%) and Wolff-Parkinson-White syndrome (13%). One or more acute metabolic crises occurred in 24 surviving children, frequently followed by developmental regression. Hyperammonaemic episodes responded well to infusion with glucose and lipid emulsion, and ammonia scavengers or haemodiafiltration. Ten-year survival was 63%, importantly for prognostication, no child died after the age of five years. CONCLUSION: TMEM70 deficiency is a panethnic, multisystemic disease with variable outcome depending mainly on adequate management of hyperammonaemic crises in the neonatal period and early childhood.
Keywords: Young Adult; acidóza laktátová; Izrael; heterozygot; Male; homozygot; mutace; retrospektivní studie; Child, Preschool; Acidosis, Lactic; Heterozygote; Turkey; mladý dospělý; Cardiomyopathies; Adolescent; Infant; Kaplan-Meier Estimate; Child; membránové proteiny; vrozené poruchy metabolismu; Europe; Membrane Proteins; dítě; Adult; Kaplanův-Meierův odhad; Disease Management; Muscle, Skeletal; dospělí; mužské pohlaví; Homozygote; kardiomyopatie; mitochondriální proteiny; mladiství; kosterní svaly; Evropa; novorozenec; předškolní dítě; Turecko; Mitochondrial Proteins; Israel; lidé; hyperamonemie; ženské pohlaví; Metabolism, Inborn Errors; Humans; Infant, Newborn; kojenec; Hyperammonemia; Mutation; Retrospective Studies; Female; management nemoci